2018
DOI: 10.1074/jbc.ra118.004963
|View full text |Cite
|
Sign up to set email alerts
|

Identification, functional characterization, and crystal structure determination of bacterial levoglucosan dehydrogenase

Abstract: Levoglucosan is the 1,6-anhydrosugar of d-glucose formed by pyrolysis of glucans and is found in the environment and industrial waste. Two types of microbial levoglucosan metabolic pathways are known. Although the eukaryotic pathway involving levoglucosan kinase has been well-studied, the bacterial pathway involving levoglucosan dehydrogenase (LGDH) has not been well-investigated. Here, we identified and cloned the gene from the bacterium and characterized the recombinant protein. The enzyme exhibited high sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
(68 reference statements)
1
18
1
Order By: Relevance
“…2 ), suggesting that LGDH reaction catalyzed by LgdA is rate-limiting in the in-vitro reconstitution reaction using LG (6 mM) as the substrate. As described above, the LGDH activity of LgdA in reverse reaction (reduction of 3-keto-LG) was higher than that in forward reaction (dehydrogenation of LG), which was consistent with our previous result in LGDH of P. phenanthrenivorans 9 . However, the addition of LgdC caused the marked degradation of LG (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…2 ), suggesting that LGDH reaction catalyzed by LgdA is rate-limiting in the in-vitro reconstitution reaction using LG (6 mM) as the substrate. As described above, the LGDH activity of LgdA in reverse reaction (reduction of 3-keto-LG) was higher than that in forward reaction (dehydrogenation of LG), which was consistent with our previous result in LGDH of P. phenanthrenivorans 9 . However, the addition of LgdC caused the marked degradation of LG (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…LGDH can also oxidize the C3-hydroxyl group of LG, which is the key reaction in the LG metabolic pathway. However, its activity toward d-glucose is very low; 0.05% and 5% activities of LG have been found in Pseudoarthrobacter and Arthrobacter LGDHs, respectively 8,9 , whereas no detectable activity toward d-glucose was observed in S-2701M LGDH in the current study (data not shown). Thus, LgdC catalyzing C3-oxidation of glucose is also thought to be a novel enzyme.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations